Composition and structural aspects of oak forests of the Sierra de Zapalinamé, Coahuila, México - Encina Domínguez, Juan Antonio; Zárate Lupercio, Alejandro; Estrada Castillón, Eduardo; Valdés Reyna, Jesús; Villarreal Quintanilla, José Ángel (Instituto de Ecología, A.C., 2009)
To determine the structure and floristic composition of the oak forest of the Sierra de Zapalinamé, we established sixty six plots of 500 m2. Density and basal area were measured for adult trees and density and cover in shrubs. Saplings were considered in concentric areas of 50 m2 and seedlings in five areas of 1 m2. All the plants were collected and identified. Vegetation attributes were used to obtain the importance value for trees and shrubs. The vascular flora takes in 259 species and infraspecific taxa with 178 genera in 67 plant families. The forest associations were defined by Quercus greggii - Q. mexicana and Quercus saltillensis - Q. laeta; the most important oaks in the forest structure were Quercus greggii (1480 ind ha-1), Q. saltillensis (876), Q. laeta (741) and Q. mexicana (284). The mature tree density (4448 ind ha-1) differs opposed to the seedlings (269 ind ha-1) and saplings (175 ind ha-1). The oaks with the highest basal area were Quercus greggii with 9.0 m2ha-1 and Q. saltillensis 6.62 m2ha-1. Thirty seven pairs of species were analyzed and 62% have significant association. The shrubs with the highest value of covering were: Garrya glaberrima, Ageratina ligustrina and A. saltillensis. The herbs were 72.9% of the flora and the most common elements were: Artemisia ludoviciana, Pleopeltis guttata, Cheilanthes tomentosa and Achillea millefolium. The species number diminishes when the altitude increases.